Respuesta :

Step-by-step explanation:

[tex] \frac{( {m}^{5} \times {m}^{6} \times {n}^{11})}{ {m}^{3} \times {n}^{5} \times n} \\ = \frac{ {m}^{11} \times {n}^{11} }{ {m}^{3} \times {n}^{6} } \\ = {m}^{8} \times {n}^{5} \\ = {m}^{8} {n}^{5} [/tex]

Answer:

[tex]\frac{m^5 \times m^6 \times n^{11}}{m^3 \times n^5 \times n^1}[/tex]

Step-by-step explanation:

m to the power of 5 = m⁵

m to the power of 6 = m ⁶

n to the power of 3 = n³

n to the power of 11 = n¹¹

      [tex]m^5 \times m^6 \times n^{11}[/tex]   over  [tex]m^3 \times n^5 \times n^1[/tex] = [tex]\frac{m^5 \times m^6 \times n^{11}}{m^3 \times n^5 \times n^1}[/tex]

Simplified form:

[tex]m^{(5+6-3)} \times n^{(11 - 5- 1)} = m^8 \times n^{6}[/tex]